Diversity of progesterone action on lipopolysaccharide‐induced expression changes in cultured human cervical fibroblasts according to inflammation and treatment timing. (1st August 2017) - Kuwabara, Yoshimitsu; Katayama, Akira; Kurihara, Sachiko; Ito, Marie; Yonezawa, Mirei; Ouchi, Nozomi; Kurashina, Ryuhei; Ichikawa, Tomoko; Sawa, Rintaro; Nakai, Akihito; Orimo, Hideo; Takeshita, Toshiyuki
Abstract : Problem: The effectiveness of progesterone (P4) treatment for preventing preterm births is unclear. Its effects on the uterine cervix were tested using cultured human uterine cervical fibroblasts (UCFs). Method of study: UCFs were incubated with lipopolysaccharide (LPS) in the presence or absence of P4 under various conditions. mRNA was subjected to PCR arrays and real‐time RT‐PCR to assess IL‐6, IL‐8, IL‐1beta, PTGS2, MMP‐1, and CXCL10 expression. Results: When exposed to a high‐LPS concentration (2.0 μg/mL), expression of these genes was not suppressed by simultaneous P4 (1.0 μmol/L) treatment, but it was significantly inhibited when P4 was administered 1 hour prior to LPS, with the exception of the chemokines IL‐8 and CXCL10 . Expression of all genes was restricted by P4 under low‐level LPS (0.2 μg/mL) stimulation, especially when administered prior to LPS treatment. Conclusion: These data suggest that early or prophylactic P4 administration is an effective and important measure for reducing preterm birth risk.